Objects for a Visual Culture of Death: Death Masks in 19th Century Spain - López de Munain, Gorka (Eikón / Imago, 2021)
Death masks have traditionally occupied a space of little importance within historical-artistic historiography. This research aims to demonstrate their outstanding role in the knowledge of the visual culture of the period in which they were created, as well as in later times. The “mascarillas” created in Spain, which have been little researched to date, can be well traced from the Spanish press, where we can find a lot of information about their various uses. But the aim of the research will not be to create a history of death masks in Spain, but to develop an analysis of them in relation to the theory of images. Thus, we will see their links with other related practices such as photography or drawing, obtained in the funerary bed, but with special importance in their connection with the memorial sculptures that were created from the mask of the deceased. Finally, we will briefly analyze all these practices in relation to post-photography, thus assuming the anachronistic nature of these images, to see how these links of the death masks with other visual manifestations continue to operate in the present.